2013
DOI: 10.1007/s12291-013-0311-6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digestive and Colon Drugs on the Human Hormones Profile

Abstract: Hormones play an important role in the digestive system. The main hormones that control digestion are gastrin, secretin, and cholecystokinin. Herein, the current study is concerned with assessing the effect of spasmo canulase and librax drugs on the human hormones profile. Blood samples were withdrawn from adult patients to measure serum FSH, E2, LH, prolactin, progesterone, DHEAS, testosterone, TSH, T3, T4, fasting insulin, and cortisol. All hormone concentrations were determined quantitatively using ELISA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…These drug-thyroid interference observations are in agreement with some previous studies indicated that nitrofurantoin and flavoxate hydrochloride drugs [7], spasmo canulase and librax drugs [8], and Allopurinol drug [9] may affect the human thyroid hormones (TSH, T3, and T4), in addition to other drugs alter TSH [10], and thyrotropin-releasing hormone receptor [11]. Therefore, it seems to go in parallel with the noteworthy elevations of the thyroid hormones in patients subjected to clemastine.…”
Section: Discussionsupporting
confidence: 92%
“…These drug-thyroid interference observations are in agreement with some previous studies indicated that nitrofurantoin and flavoxate hydrochloride drugs [7], spasmo canulase and librax drugs [8], and Allopurinol drug [9] may affect the human thyroid hormones (TSH, T3, and T4), in addition to other drugs alter TSH [10], and thyrotropin-releasing hormone receptor [11]. Therefore, it seems to go in parallel with the noteworthy elevations of the thyroid hormones in patients subjected to clemastine.…”
Section: Discussionsupporting
confidence: 92%
“…Sex differences have been noted with regard to abdominal pain sensitivity in general and in patients with IBS [106][107][108][109]. Indeed, a study of Librax ® also found sex differences in men versus women which may determine visceral pain responses to this therapy [110]. Since no one therapy manages a majority of symptoms in IBS patients, Donnatal ® and other combination drugs, though older, are still viable alternatives for the treatment of this difficult condition with safety which has been proven over decades of use.…”
Section: Resultsmentioning
confidence: 99%